Perubahan Morfologi Kali Garang - Banjir Kanal Barat Tanpa Bendung Simongan (Pendekatan Model Simulasi BRI-STARS) - Edhisono, Soetarto (MEDIA KOMUNIKASI TEKNIK SIPIL, 2006)
The changing of land-use on the upper Simongan Weir causes the increasing of flood discharge. It was shown during flood that occured on January 1990, which in that time flood water overtopped of the dikes and caused dikes collapsed in some places and flood was ocurred around Simongan area. This research was  made because there was  a plan to change the Simongan Weir into barrage, in order to make flood water level of  the Garang River  lower during flood. The crest of the Simongan Fixed Weir would be cutted in 3.7 m height  in order to make flood water level lower, and to keep the water level remain the same during normal condition, some gates would be installed above the cutted weir crest as barrages. This situation would change river morphology of the Garang River and  West Flood Way. This paper was contained simulation result  of  the changing of river morphology of the Garang River and West Flood Way without Simongan Weir by using BRI-STARS ( BRIdge Stream Tube model for Alluvial River Simulations ) software. This simulation model generated  semi-two dimensional water  flows and its sediment which capabled to compute scouring and silting on sub-critical, super critical flows and combination of these both flows conditions.Keywords:  weir, barrage, morphology, scouring, siltationPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3950[How to cite: Edhisono, S., 2006, Perubahan Morfologi Kali Garang - Banjir Kanal Barat Tanpa Bendung Simongan (Pendekatan Model Simulasi  BRI-STARS), Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 3, pp. 240-250]